'I've worked so hard, I deserve a snack in the worksite cafeteria': A focus group study. (1st February 2019) - Velema, Elizabeth; Vyth, Ellis L.; Steenhuis, Ingrid H.M.
Abstract: This study obtained insight in motivation regarding food choices of Dutch employees, especially when visiting the worksite cafeteria. We also aimed to know why employees visit the worksite cafeteria. These insights are useful for intervention development to encourage healthier purchases in worksite cafeterias. We conducted seven focus groups among 45 employees of seven Dutch companies. The topics were 1) drivers and motives for food selection; 2) motives for visiting the worksite cafeteria; 3) motives for food selection in the worksite cafeteria; 4) perceptions of healthiness of products in the worksite cafeteria and 5) solutions brought up by the employees to encourage healthier eating. Thematic analyses were conducted with MAXQDA software. Qualitative analyses revealed that this group of Dutch employees mentioned 'healthiness', 'price' and 'taste' as most important drivers food selection. These employees generally visit the worksite cafeteria to have a break from their work setting. Healthiness played a less important role in visiting or making food choices in the worksite cafeteria. Reasons for buying unhealthy food items were being tempted and the feeling to 'deserve' it. In order to choose healthier foods employees suggested a bigger offer of healthy food options, providing knowledge, changing prices and prominent placing of healthy foods. This focus group study shows that drivers for food selection can differ from motives for visiting the worksite cafeteria and when choosing food there. Health is important for food choice in general, but less important in the worksite cafeteria. The results of this study could be used in the development of strategies that aim to change people's food choice behavior.